1992
DOI: 10.1007/bf01203758
|View full text |Cite
|
Sign up to set email alerts
|

Successful parents of in vitro fertilization (IVF): The social repercussions

Abstract: A matched comparison was made of 157 parents of preschool twins conceived by one of the following: in vitro fertilization (IVF), infertility workup combined with infertility drug treatment, or spontaneously. The Interview Schedule for Social Interaction was used to examine systematically a comprehensive range of social relationships and the asymmetries therein. Overall, IVF parents reported having deficient social relationships compared with non-IVF parents, and this deficiency was both in size and in affectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Findings from this study with MAR twins may generalize to twins conceived without fertility treatments, but differences between families with MAR and non‐MAR children should be considered when attempting this generalization. Parents who conceive children after MAR may have diminished social support and parenting efficacy compared with parents who did not use fertility treatments to conceive children (Hammarberg, Fisher, & Wynter, ; Munro, Ironside, & Smith, ); these constructs are related to poorer parent–child relationship quality (Belsky, ). Families that use MAR to conceive children are often more aware of twin risks, and in some MAR treatments such as IVF, parents can make treatment decisions to increase the probability of twins due to a desire for twin births (Sharara, ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study with MAR twins may generalize to twins conceived without fertility treatments, but differences between families with MAR and non‐MAR children should be considered when attempting this generalization. Parents who conceive children after MAR may have diminished social support and parenting efficacy compared with parents who did not use fertility treatments to conceive children (Hammarberg, Fisher, & Wynter, ; Munro, Ironside, & Smith, ); these constructs are related to poorer parent–child relationship quality (Belsky, ). Families that use MAR to conceive children are often more aware of twin risks, and in some MAR treatments such as IVF, parents can make treatment decisions to increase the probability of twins due to a desire for twin births (Sharara, ).…”
Section: Discussionmentioning
confidence: 99%
“…Religious dilemmas were reported by Catholic and Jewish respondents in the Pettee report. Respondents recommended that couples who are considering the donor egg option develop a support network, which is noteworthy in light of another study (Munro, Ironside, & Smith, 1992) reporting deficient social relationships in IVF parents compared with non-IVF parents.…”
mentioning
confidence: 99%
“…Only a few studies have examined differences in families with twins conceived via IVF/OI and those conceived naturally. Munro, Ironside, and Smith (1992) compared 80 families with pre‐school age twins conceived naturally or after IVF and found that parents who conceived their twins after IVF showed poorer social support than non‐IVF parents. Cook, Bradley, and Golombok (1998) compared 12 families with four‐ to eight‐year‐old twins conceived after IVF to 14 twin pairs naturally conceived and found that the IVF group reported greater parenting stress but no differences in parenting quality or child behaviour.…”
mentioning
confidence: 99%
“…While many studies with singletons have found parenting in IVF families to be superior to parenting in naturally conceived families, these findings have not been observed in the few studies that have been done with families with twins. The few studies which have examined the effects of IVF/OI in families of twins have suffered from methodological problems such as small sample sizes and control groups that are poorly matched for confounding variables, such as maternal age and number of older children (Colpin et al, 1999; Cook, Bradley, & Golombok, 1998; Munro et al, 1992). In addition, these studies have obtained eligible families from a select number of fertility programmes or hospitals, so it is possible that their samples are not representative of the population who have conceived twins after IVF and OI.…”
mentioning
confidence: 99%